2023
DOI: 10.3390/ijms241311149
|View full text |Cite
|
Sign up to set email alerts
|

MCL1 Inhibition Overcomes the Aggressiveness Features of Triple-Negative Breast Cancer MDA-MB-231 Cells

Abstract: Triple-Negative Breast Cancer (TNBC) is a particularly aggressive subtype among breast cancers (BCs), characterized by anoikis resistance, high invasiveness, and metastatic potential as well as Epithelial–Mesenchymal Transition (EMT) and stemness features. In the last few years, our research focused on the function of MCL1, an antiapoptotic protein frequently deregulated in TNBC. Here, we demonstrate that MCL1 inhibition by A-1210477, a specific BH3-mimetic, promotes anoikis/apoptosis in the MDA-MB-231 cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…However, this small-scaled exploratory study has indicated that activated intra-tumor immune microenvironments may play an important role in pathological responses to NAC, and that the up-regulation of vimentin and v+ in the residual tumors may be pivotal prognostic factors in non-pCR cases to NAC. Enhancement of intra-tumor immunity before the NAC introduction using pre-operative radiotherapy or immunepotentiating agents might provide a greater anti-tumor activity of NAC [27][28][29]. Additionally, anti-EMT agents together with NAC might improve the outcome of patients with TNBCs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, this small-scaled exploratory study has indicated that activated intra-tumor immune microenvironments may play an important role in pathological responses to NAC, and that the up-regulation of vimentin and v+ in the residual tumors may be pivotal prognostic factors in non-pCR cases to NAC. Enhancement of intra-tumor immunity before the NAC introduction using pre-operative radiotherapy or immunepotentiating agents might provide a greater anti-tumor activity of NAC [27][28][29]. Additionally, anti-EMT agents together with NAC might improve the outcome of patients with TNBCs [30,31].…”
Section: Discussionmentioning
confidence: 99%